Variability and genetic divergence in paprika (Capsicum annuum L.) 1 - C Ravi Sankar, S Surya Kumari, K Uma Jyothi, D Srihari, A Siva Sankar (Journal of Spices and Aromatic Crops, 2010)
Ninety four paprika (Capsicum annuum) accessions were evaluated for 17 characters forvariability, heritability, genetic advance and genetic divergence at Lam, Guntur (AndhraPradesh). Higher phenotypic and genotypic coefficient of variation (PCV and GCV) andheritability coupled with high genetic advance was observed for number of fruits plant-1,fresh fruit yield plant-1, dry fruit yield plant-1, 100 seed weight, number of seeds fruit-1 andcapsanthin, capsaicin and oleoresin contents indicating the higher magnitude of variabilityfor these traits and consequently more scope for their improvement through selection. Plantheight, plant spread and fruit diameter exhibited moderate PCV and GCV estimates suggestingthe possible role of environment in expression of these characters. Cluster analysis throughMahalanobis D2 analysis classified the 94 genotypes into 10 clusters indicating considerablegenetic diversity in the material studied.